Trauma-Informed Social Work for Sustainable Well-Being: Practices, Challenges, and Future Directions - Kamal Abdo, Badr Aldin; Alkhamissi, Aisha Reden; Alkhamissi, Aisha Reden (European Journal of Sustainable Development, 2025)
This study aims to identify the professional competencies required of student mentors when utilizing evidence-based practices to address adolescent trauma. Additionally, it evaluates the effectiveness of a targeted intervention program designed to enhance these competencies. A mixed-methods research approach was employed, incorporating both quantitative and qualitative data collection tools. The quantitative component utilized a professional competency dimensions scale, while the qualitative aspect involved semi-structured interviews. The study population consisted of student mentors working at the middle and secondary school levels in Jeddah, with a sample of 30 mentors participating. Quantitative findings revealed statistically significant differences in the participants’ mean scores on the evidence-based practice scale (covering knowledge, values, and skills) before and after the intervention, with a significance level of p = .00, indicating improvements across all measured dimensions. Qualitative data further highlighted enhancements in mentors’ knowledge and self-confidence, shifts in practice through the adoption of new strategies, and a greater appreciation for the professional values associated with evidence-based practice. Participants also emphasized the importance of involving practitioners in the design of future training initiatives. Based on these findings, the study recommends the ongoing professional development of mentors in evidence-based practices and the creation of specialized training programs—particularly targeting younger and newly graduated mentors—to build a strong foundation of knowledge and practical skills. It also underscores the need to develop mentors’ research and evaluation capabilities Keywords: trauma-informed practice, social work, adolescent well-being, sustainability, vocational training, evidence-based practice